Probabilistic Fatigue Crack Initiation and Propagation Fields Using the Strain Energy Density - Correia, J.A.F.O.; Huffman, P.J.; De Jesus, A.M.P.; Lesiuk, G.; Castro, J.M.; Calcada, R.A.B.; Berto, F. (Проблемы прочности, 2018)
Recently, Huffman developed a strain energy density based on Walker-like stress life and fatigue crack growth behavior. In this paper, the Huffman model based on local strain energy density is used to predict the fatigue crack initiation and propagation for the P355NL1 pressure vessel steel. This model is combined with the generalized probabilistic fatigue model proposed by Correia aiming the generation of probabilistic fatigue crack initiation and propagation fields. In this study, the local stress and strains at the crack tip were obtained combining linear-elastic and elastoplastic analyses. The probabilistic fatigue crack growth rates fields for several stress R-ratios are estimated considering strain, SWT and equivalent stress amplitude damage parameters. A comparison between the experimental fatigue crack growth (FCG) data and the generated probabilistic FCG fields is made with very satisfactory correlations being found.